2021
DOI: 10.3390/ijms222011097
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of SRT1720 Treatment on Endothelial Cells Derived from the Lung and Bone Marrow of Young and Aged, Male and Female Mice

Abstract: Angiogenesis is critical for successful fracture healing. Age-related alterations in endothelial cells (ECs) may cause impaired bone healing. Therefore, examining therapeutic treatments to improve angiogenesis in aging may enhance bone healing. Sirtuin 1 (SIRT1) is highly expressed in ECs and its activation is known to counteract aging. Here, we examined the effects of SRT1720 treatment (SIRT1 activator) on the growth and function of bone marrow and lung ECs (BMECs and LECs, respectively), derived from young (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…All tissue isolation was performed in a sterile environment. LECs and BMECs were isolated from neonatal mice (2-6 days of age) as described previously ( 4 , 32 , 33 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All tissue isolation was performed in a sterile environment. LECs and BMECs were isolated from neonatal mice (2-6 days of age) as described previously ( 4 , 32 , 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tube formation was assessed by Matrigel tube formation assay as previously described ( 32 , 34 ). Matrigel basement membrane matrix (Corning ® , Corning, NY) was polymerized in 96-well plates (50μl/well) at 37°C and 5% CO 2 for 45 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…SRT1720 is a synthetic compound that activates SIRT1(( Minor et al, 2011 ; Svensson et al, 2015 )) and has been implicated in the regulation of neurogenesis ( Iwata et al, 2020 ) and angiogenesis ( Dadwal et al, 2021 ) through activation of SIRT1. It has also been shown that SRT1720 can reduce pain due to bone cancer ( Li et al, 2019 ) and intervertebral disc degeneration ( Zhang et al, 2020 ) by activating SIRT1.…”
Section: Potential Drugs and Strategies To Treat Oa By Affecting The ...mentioning
confidence: 99%